China and International Student Mobility - Gao, Hang; de Wit, Hans (International Higher Education, 2017)
China has the objective to receive 500,000 international students at the end of this decade, and is already moving fast in this direction, bypassing Australia, France, and Germany, to become the third destination country after the United States and the United Kingdom in hosting international students. With the current political climate in the main countries hosting international students, China’s perspectives to become a dominant player are more optimistic than a few years ago. Attracting international students and increasing their stay-rate after graduation is becoming a major political strategy at the national level and also for the main cities and provinces, as well as the universities. But, to be sustainable in this effort, China’s higher education system needs to work on the quality of its education and services.